Exploring factors of open educational resources (OER) in Zambian community schools: A qualitative study - Enala Sharon Lufungulo; Jiyou Jia; Kennedy Mwila (Social Sciences and Humanities Open)
Historically, copyright regulations have posed challenges in the dissemination of educational resources, leading to financial barriers, limited access, and outdated materials. Open Educational Resources (OER) offer free access to materials, addressing these issues and promoting equitable learning globally. This study examines the integration of OERs among primary school educators in Zambian community schools. Grounded in Connectivism, Diffusion of Innovations Theory, and the OER Adoption Pyramid, this research explores how personal values, institutional support, technology, OER awareness, and cultural reception influence educators' decisions to adopt OER. Data were collected through in-depth interviews with 34 participants, two focus group discussions, document analysis, and social media data. The study was conducted in Lusaka and Chipata, focusing on participants actively involved in using OER provided by an NGO in collaboration with Zambia's Ministry of Education. The findings highlight the significant role of individual preferences, institutional frameworks, and infrastructure in OER adoption. It emphasises the importance of policy development, professional training, and capacity building to overcome barriers. While this study is limited in scope, it advocates for future research on nationwide OER adoption, policy impact, and sustainability to deepen understanding and foster inclusive OER integration.